The Examined Side: The Role of Congregations in Clergy Transitions - C. Franklin Granger; Lorilee R. Sandmann (Adult Education Research Conference, 2009)
The transition from theory to practice in the move from seminary to congregational ministry remains a risky leap for clergy despite curricular reforms and addition of context-based learning during professional education. Congregations that serve as teaching environments provide valuable practical ministry training for early-career clergy.